Integration and scale-up of efforts to measure and reduce HIV-related stigma: the experience of Thailand - Taweesap Siraprapasiri (2020)
OBJECTIVE(S): To share Thailand's journey to develop and implement a national response to measure and tackle HIV-related stigma and discrimination and key implementation lessons learned. DESIGN: A national response to stigma and discrimination including policy, measurement, and interventions. Intervention activities began in health facilities because of their key role in achieving health outcomes. METHODS: Three building blocks were implemented: policy and its translation into a roadmap for action; measurement development and routinization to inform intervention design and track progress; and intervention development and implementation. RESULTS: Thailand has successfully integrated a response to stigma and discrimination into its national HIV response. Stigma and discrimination-reduction was included as a key strategic goal for the first time in the 2014-2016 National AIDS Strategic Plan. A costed national stigma and discrimination-reduction roadmap incorporated into the operational plan provided clear strategic direction on how to move forward. The development of HIV-related stigma and discrimination measures and their incorporation into the national HIV monitoring and evaluation framework has led to routine data collection to monitor stigma and discrimination in health facilities, key populations, and the general population. Development and successful piloting of a health facility stigma-reduction package - the 3 × 4 approach - has led to national scale-up of the approach through a modified approach. Thailand continues to evolve and innovate the program, including developing new activities to tackle stigma and discrimination beyond the health system. CONCLUSION: Thailand's experience demonstrates the key elements needed to make addressing stigma and discrimination a priority in the national HIV response.